Customers of common fashion brands int the Czech republic: innovators and opinion leaders - Novotová, Jitka (Univerzita Pardubice, 2018)
This article concentrates on the identification of special customer categories known as innovators and opinion leaders, also collectively called Fashion Leaders. The article focuses only on customers buying clothing of medium price and quality, known as Common Brands clothing. The categories of Innovators and Opinion Leaders in this article were measured on the basis of rating scales from renowned international authors. Confirmation factor analysis confirmed that the rating scales belong to latent variables and also sufficiently explain them. The result of the correlation analysis proved that the Innovator and Opinion Leader categories strongly correlate and therefore may be measured jointly in subsequent research, as one shared category of Fashion Leaders. Differences between demographic characteristics of Fashion Leaders and Fashion Non- Leaders were identified using the two-sample t-test. It was particularly found that women with lower education who shop very often are Fashion Leaders. The results of this research may be used as a basis for further customer surveys of Common Brands in the Czech Republic. The practical contribution of this article is the identification and description of the Fashion Leaders customer segment that can help fashion producers in promoting new collections or raising awareness in the fashion field.
Keywords: fashion; customer; fashion leaders; innovators; opinion leader; common fashion brands; C38; M31